Microseconds and Macropolicy - Wriston, Walter B. (Tufts Archival Research Center, 2007)
This document was created from the article, "Microseconds and Macropolicy" by Walter B. Wriston for the March/April 1985 edition of "Regulation: AEI [American Enterprise Institute] Journal on Government and Society." The original article is located in MS134.003.026.00019.